Avaliação fármaco-molecular de novos hidroxamatos sintéticos como protótipos antitumorais: predição in silico, validação in vitro e aplicação em nanosistemas metálicos. - Luciano, Maria Cláudia dos Santos (2019)
This thesis is presented in five chapters that contain: (1) Literature review on epigenetic drugs publiched; (2) In silico evaluation of three hydroxamates compounds; (3) Validation in vitro of hypotheses generated in silico after determination of biological activity and molecular mechanisms related to cytotoxic activity of these compounds; (4) Evaluation of the cytotoxic effect of these compounds in the presence of copper sulfate and (5) Development of metallic nanosystems for hydroxamate class and evaluation of their synergistic effect in multi-drug therapy in vitro. Thus, the objective of the present work was to evaluate the pharmacological and molecular potential in silico, validate the hypothesis through cellular and molecular evaluation in vitro of two hydroxamate class prototypes (LDT565 and LDT566) as potential antitumor agents and nanotechnology application. To achieve the proposed objectives, the hypotheses were validated through the use of cytotoxicity techniques (MTT, SRB, XCelligence and Prestoblue); the morphological and molecular characteristics were evaluated by (Flow Cytometry; Optical Microscopy; Western Blot; RT-qPCR and High Content Screening) and for biotechnological application the nanoencapsulation were performed in metallic nanolipids. Five common targets were identified in silico among the three hydroxamates (Z score <-0.5), three of them related to mitochondrial metabolism and two with transcriptional regulators. The observed in silico ADMEtox profiles indicate that the three compounds have the main pharmacokinetic differences related to metabolism. The in vitro cytotoxic in the cell lines HL60, RAJI, JURKAT and K562 presented IC50 ranging from 1.43 to 54.06 µM LDT565 and 2.59 to 22.48 µM for LDT566, respectively. The molecular evaluation indicated a depletion of gene expression in HDAC 1, HDAC 2 and HDAC 10 transcripts without causing enzymatic inhibition of HDACs. The protein expression data indicate a marked effect on mitochondria with significant changes in transmembrane potential and differential expression of proteins such as BCL-xL, BIM and BAX. Both compounds caused cell cycle arrest in G0/G1, with significant increase in subG1 levels. Morphological changes showed reduction in cell size and induction of apoptosis in early stage after 48h. The compound LDT566 had a significant increase in cytotoxic effect in vitro when associated with copper sulfate, inducing significant cellular and molecular changes, with depletion of metalloproteinase gene expression (MMP14). The LDT566 compound had pharmacological characteristics compatible with nanocapsulation technology in metallic systems, presenting encapsulation rates of 70%, and synergistic/additive potential when in muti-drug treatment in vitro associating Hydroxamate-Irinotecan. The conclusions point a strong correlation between in silico predictions and in vitro experimental findings. The hydroxamates LDT565 and LDT566 showed selective cytotoxic potential equivalent to the positive control Vorinostat. LDT566 presented a profile compatible with copper sulphate-dependent for encapsulation sucess and can be considered as a new prototype potentially applicable in preclinical models.